Seasonal Variations of Natural Organic Matter (NOM), Residual Chlorine, and pH in Water Distribution Networks of Shiraz City - Zeynab Tabatabaei; Mohammad Ali Baghapour; Vafa Lotfi; Amin Samzadeh (Shiraz University of Medical Sciences, 2021)
Background: Natural Organic Matters (NOMs) react in the presence of residual chlorine in distribution network pipes, producing such byproducts as Trihalomethanes which are carcinogenic and mutagenic. The present study was conducted to investigate the quality of drinking water in Shiraz. Methods: In this cross-sectional study, 54 samples were taken from 27 locations in both summer and winter. For each sample, temperature, residual chlorine, pH, and NOM were measured during the two seasons. Residual chlorine and temperature measurement were performed at the sampling sites, but pH and NOM were measured in the laboratory. Results: According to the results, the mean concentrations of Total NOM (TNOM), residual chlorine, pH, and temperature varied from 0.9 to 5 m-1, 0 to 1.2 mg/L, 7.4 to 8 and 18 to 23.5 ᵒC in summer and from 0.3 to 1.5 m-1, 0 to 0.8 mg/L, 7.6 to 8.2 and 9.7 to 10.8 ᵒC in winter, respectively. In addition, the concentrations of all measured parameters, except for pH, were reported to be higher in summer than in winter. Conclusion: As a result, since the amount of NOM in the drinking water distribution network of Shiraz was not zero, regular monitoring of these compounds in the distribution networks is recommended to be done by engineers.